2020
DOI: 10.1016/j.jcf.2020.10.003
|View full text |Cite
|
Sign up to set email alerts
|

The global impact of SARS-CoV-2 in 181 people with cystic fibrosis

Abstract: Highlights We report 181 people with CF from 19 countries diagnosed with SARS-CoV-2 Spectrum of outcomes observed was similar to that seen in the general population 11 people were admitted to intensive care and 7 died Three of the people who died had received an organ transplant Lower lung function and having been transplanted may be linked to hospitalisation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
104
3
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(119 citation statements)
references
References 6 publications
9
104
3
3
Order By: Relevance
“…Very recently, the international Cystic Fibrosis Registry Global Harmonization Group published in this Journal interesting data on the clinical characteristics and outcomes of SARS-Cov-2 infection in CF patients. [2] …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, the international Cystic Fibrosis Registry Global Harmonization Group published in this Journal interesting data on the clinical characteristics and outcomes of SARS-Cov-2 infection in CF patients. [2] …”
mentioning
confidence: 99%
“…These data are in accordance with those reported by the clinical studies of the global project. [2] .…”
mentioning
confidence: 99%
“…In particular, an early multinational report on 40 CF cases highlighted good recovery from SARS-CoV-2 in the heterogeneous 40-subject CF cohort, with a total absence of mortality that may derive from the relatively low incidence of the novel coronavirus amongst the CF population [ 155 ]. A subsequent report involving a larger international cohort (181 people with CF) confirmed that SARS-CoV-2 infection for most people with CF may be less severe than originally feared, although it can result in serious consequences for some CF patients (with older age, CF-related diabetes, lower lung function, and recipients of an organ transplant) [ 156 ]. Moreover, it has recently emerged that a one-month-old infant with CF and SARS-CoV-2 positivity did not display any COVID-19 symptoms, suggesting that the low pathogenicity observed in healthy children applies to young CF patients as well [ 157 ].…”
Section: Potential Impact Of Covid-19 On Inflammation In Cf Patienmentioning
confidence: 99%
“…As we transition into the winter months marked with a significant rise of SARS-CoV-2 in many parts of the country, it remains imperative that we continue collecting survey data. This effort paired with others across the globe [7] with allow us to monitor and report out on the impact of SARS-CoV-2 on clinical trials networks as well as the health and well-being of people with CF.…”
Section: Next Stepsmentioning
confidence: 99%